Komunikasi kesehatan bagi pelajar dengan pendekatan peer education - Chotijah Fanaqi; Fadilah Nurkalam; Dhea Ayuning Tias; Silvia Dwi Syahputri; Novi Octaviani (Penerbit Goodwood, 2020)
Purpose: Health communication has a strategic role in minimizing the risk of Covid-19 transmission. This is because the public's understanding of the implementation of the health protocols recommended by the government has not been implemented equally among all groups. One of the community groups that is quite vulnerable is a group of students in Kampung Lengkong Kaler, Desa Samarang, Kecamatan Samarang, Kabupaten Garut, who carry out offline learning activities as an additional effort of online learning which is carried out only twice a week. This activity happens to be a cluster for the spread of the virus if there is no health protocol such as the use of masks. The purpose of this activity is as an effort to prevent the spread of Covid 19 through Health Socialization to adolescents. Research methodology: The methodology used in this activity is health socialization and offline learning assistance to adolescents using the Peer Education approach. Peer educators or peer educators are proven to have considerable potential at adolescence in terms of attitudes. This is caused by peers who represent an attitude of acceptance, and there is motivation for adolescents who acknowledge by their group. Results: There was a change in behavior and the application of new habits through post-socialization health protocols and assistance to adolescents who were members of the study groups in Lengkong Kaler Village. Limitation: The inhibiting factor for health socialization activities with a peer education approach is the limited media space that represents students to conduct socialization simulations to their peers. Contribution: The solution to the existing obstacles is to use the Garut University Service Team post on loan by local residents. Keywords: Health communication, Socialization, Peer education